Designing and Piloting a Tool for the Measurement of the Use of Pronunciation Learning Strategies - Pawlak, Mirosław (Research in Language, 2010)
Despite the fact that the last few years have witnessed a growth of interest in pronunciation learning strategies (PLS) (e.g. Petersen 2000; Pawlak 2008a; Wrembel 2008), this line of inquiry still remains neglected and is in urgent need of further empirical investigation. This is because the available research findings are primarily confined to the identification and description of the strategic devices that learners draw upon in their attempts to learn the various segmental and suprasegmental features, with only a handful of studies addressing such issues as the factors influencing PLS choice and use, the impact of proficiency levels or the value of strategies-based instruction in this area. Another problem is related to the use of diverging research methodologies and data collection tools, which renders it impossible to make comparisons between various studies, view their results in a cumulative way and arrive at conclusions concerning the effectiveness of specific strategies used by learners. What appears to be indispensable to drive the field forward and ensure that research findings will be comparable across studies and provide a sound basis for feasible pedagogic proposals is to draw up a classification of PLS and design on that basis a valid and reliable data collection tool which could be employed to measure the use of these strategies in different groups of learners, correlate it with individual and contextual variables, and appraise the effects of training programs. In accordance with this rationale, the present paper represents an attempt to propose a tentative categorization of pronunciation learning strategies, adopting as a point of reference the existing taxonomies of strategic devices (i.e. O'Malley and Chamot 1990; Oxford 1990) and the instructional options teachers have at their disposal when dealing with elements of this language subsystem (e.g. Kelly 2000; Goodwin 2001). It also introduces a research instrument designed on the basis of the classification that shares a number of characteristics with Oxford's (1990) Strategy Inventory for Language Learning but, in contrast to it, includes both Likert-scale and open-ended items. The findings of a pilot study which involved 80 English Department students demonstrate that although the tool requires considerable refinement, it provides a useful point of departure for future research into PLS.